ANALISIS PREDIKSI PERINGKAT OBLIGASI SYARIAH - Syarif-Universitas Bina Sarana Informatika, Mahmud (APMMI - Asosiasi Profesi Multimedia Indonwsia, 2019)
Abstract-This study discusses the Prediction Analysis Bond Rating Sharia, in Indonesia there are two debt securities rating agencies namely PT. PEFINDO (Securities Rating Indonesia), and Kasnic Credit Rating Indonesia. Shariah based financial concepts today are growing rapidly. One form of shariah financial instruments which have been widely published both by corporate and state is a sukuk. In this study used five financial ratios as follows: Leverage, Liquidity, Solvability, Profitability and Productivity. This study wanted to test whether the proxy fifth ratio and can form a bond rating prediction model. Based on the criteria defined, gained as much as 34 observations Islamic bond ratings as a sample. From the results of these observations can be deduced. Results of the independent testing of difference (t-test) demonstrated statistically proven that there is a difference between financial ratios (leverage, liquidity, solvency, profitability, productivity) companies that sharia bond ratings fall into the strong and adequate grade. By looking at these results, the first hypothesis (H1) is accepted, and the results of testing discriminant analysis (Multiple Discriminant Analysis) suggests that statistically financial ratios can form a bond rating prediction model two years of observation (2012-2014)Keyword : Financial Ratios, ranking Bonds, Islamic Bonds Abstrak-Penelitian ini membahas tentang Analisis Prediksi Peringkat Obligasi Syariah, Di Indonesia ada dua lembaga pemeringkat sekuritas hutang yaitu PT. PEFINDO (Pemeringkat Efek Indonesia), dan Kasnic Kredit Rating Indonesia. Konsep keuangan berbasis syari’ah saat ini sedang tumbuh secara cepat. Salah satu bentuk instrumen keuangan syari’ah yang telah banyak diterbitkan baik oleh korporasi maupun negara adalah sukuk. Pada penelitian ini digunakan lima rasio keuangan yaitu: Leverage, Liquidity, Solvability, Profitability, dan Productivity. Penelitian ini ingin menguji apakah kelima rasio dan proksi tersebut dapat membentuk model prediksi peringkat obligasi. Berdasar dari kriteria yang ditetapkan, diperoleh sebanyak 34 pengamatan peringkat obligasi syariah sebagai sampel. Dari hasil pengamatan tersebut dapat di tarik kesimpulan. Hasil pengujian beda independen (uji t-test) menunjukkan bahwa secara statistik terbukti terdapat perbedaan antara rasio keuangan (leverage, likuiditas, solvabilitas, profitabilitas, produktivitas) perusahaan yang peringkat obligasi syariahnya termasuk ke dalam strong dan adequate grade. Dengan melihat hasil tersebut maka hipotesis pertama (H1) diterima, dan Hasil pengujian analisis diskriminan (Multiple Discriminant Analysis) menunjukkan bahwa secara statistik rasio keuangan dapat membentuk model prediksi peringkat obligasi selama dua tahun pengamatan (2012 - 2014). Kata kunci : Rasio Keuangan, Peringkat Obligasi, Obligasi Syariah